Papillary carcinoma of male breast: the uncommon pathology of breast cancer - Mohamad, Ikhwan Sani; Che Alhadi, Shahidah; Wan Muhamad Mokhter, Wan Muhamad Mokhzani; Zakaria, Zaidi (Longdom Publishing, 2013)
Breast cancer in men is uncommon. It represents less than 1% of all cancer in men. The survival rates of breast cancer are similar in men and women. Papillary carcinoma of breast is an extremely rare form of breast cancer. It tends to affect older age group but had excellent prognosis.